The correlation between students’ skill on context clues and their reading comprehension skill of eleventh graders at SMA Negeri 2 Nganjuk - Penta Miyanti, Arundina; Sujono, sujono (STKIP PGRI Nganjuk, 2024)
The use of context clues can improve reading comprehension by understanding difficult words and expanding readers’ vocabulary. This study aims to (1) identify students' context clues skill, (2) identify students' reading comprehension skill, (3) determine the correlation between students' context clues and reading comprehension skill. A quantitative approach with a correlation research design was used. The sample was 70 students obtained by convenience sampling. Data was collected by test using worksheets. The findings showed diversity in students' score. The highest student score in context clues was in antonym with a percentage of 67.85% and in reading comprehension was in vocabulary with a percentage of 62.85%. The lowest percentage are definition and example, 59.28%, also the main idea with the percentage of 60%. The results of the significance value of 0.000 and Pearson correlation of 0.970 showed a very strong relationship between both variables. Kata Kunci—petunjuk konteks, pemahaman membaca